2011
DOI: 10.1007/s10803-011-1216-y
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy and MRI Reveal No Evidence for Brain Mitochondrial Dysfunction in Children with Autism Spectrum Disorder

Abstract: Brain mitochondrial dysfunction has been proposed as an etiologic factor in autism spectrum disorder (ASD). Proton magnetic resonance spectroscopic imaging ((1)HMRS) and MRI were used to assess for evidence of brain mitochondrial dysfunction in longitudinal samples of children with ASD or developmental delay (DD), and cross-sectionally in typically developing (TD) children at 3-4, 6-7 and 9-10 years-of-age. A total of 239 studies from 130 unique participants (54ASD, 22DD, 54TD) were acquired. (1)HMRS and MRI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…It should be noted that, although controversial, some investigators have reported that a low NAA is a marker of mitochondrial dysfunction and is consistent with inhibition of mitochondrial respiratory chain function (Bates et al 1996;Boumezbeur et al 2010;Clark 1998). For the present study (Corrigan et al 2011), the authors did not report if they measured any other metabolites besides lactate on MRS such as NAA. Based upon their previous studies, it would be unusual if they did not acquire NAA levels.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…It should be noted that, although controversial, some investigators have reported that a low NAA is a marker of mitochondrial dysfunction and is consistent with inhibition of mitochondrial respiratory chain function (Bates et al 1996;Boumezbeur et al 2010;Clark 1998). For the present study (Corrigan et al 2011), the authors did not report if they measured any other metabolites besides lactate on MRS such as NAA. Based upon their previous studies, it would be unusual if they did not acquire NAA levels.…”
mentioning
confidence: 64%
“…Since a lactate peak is a marker of mitochondrial dysfunction, the authors suggest that their study finds no evidence of mitochondrial dysfunction in children with ASD and suggest that this finding supports the idea that there is no association between mitochondrial dysfunction and ASD. While their findings are interesting and certainly add to the understanding of the complex biochemical abnormalities associated with ASD, we believe that the findings from Corrigan et al (Corrigan et al 2011) neither support nor refute an association between mitochondrial dysfunction and ASD for several reasons which we will outline below. We are particularly concerned that the results of this study will result in parents being told that mitochondrial disease has been ruled out (''No Evidence for Brain Mitochondrial Dysfunction'') based on a test that has very poor sensitivity.…”
mentioning
confidence: 91%
See 3 more Smart Citations